Analisis Perbandingan Harga dan Kualitas Pelayanan Terhadap Kepuasan Konsumen pada Kopi Kenangan dan Tomoro Coffee di Surakarta - Cristiana, Elysa; Wulandari, Dewi; Utari, Syila Aviva Nur; Rahadhini, Marjam Desma (Lembaga Pengembangan Kinerja Dosen, 2025)
This study seeks to examine the effect of price and service quality on customer satisfaction across two coffee beverage brands, specifically Kopi Kenangan and Tomoro Coffee. This study focuses on assessing how much each variable, both separately and together, impacts customer satisfaction at the two coffee outlets. This research outlines the theories related to price, service quality, and customer satisfaction. Data collection was carried out by distributing questionnaires to customers of both coffee brands, and the data were then analyzed quantitatively through tests of validity, reliability, and linear regression. The analysis results indicate that both service quality and price significantly affect customer satisfaction, both independently and simultaneously. Kopi Kenangan is considered superior in terms of competitive prices and fast service, while Tomoro Coffee stands out in menu variations and a more personalized customer experience. The study concludes that enhancing service quality and implementing strategic pricing can positively influence customer satisfaction and loyalty within the coffee beverage sector.